2020
DOI: 10.21037/jtd.2020.04.01
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between fractional exhaled nitric oxide and Asthma Control Test score and spirometry parameters in on-treatment- asthmatics in Ho Chi Minh City

Abstract: Background: Although fractional exhaled nitric oxide (FeNO) is a reliable and easily applied marker of airway inflammation in asthma, the relationship between FeNO and indicators of asthma control [Asthma Control Test (ACT) score] and/or severity (spirometry parameters) remains unclear. This study aims to determine possible correlations between FeNO and ACT score; and between FeNO and spirometry parameters. Methods: A cross-sectional study with convenience sampling was conducted among ambulatory patients in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“… 41 Moreover, significant differences in FeNO were seen between different asthma control groups. 41 Additionally, other studies indicated that FeNO values were related to several markers of asthma control, such as nighttime symptoms, beta-agonist use, and bronchodilator reversibility, 42 as well as to the use of oral or inhaled steroid treatment. 43 In addition, previous studies showed that FeNO was raised in asthmatic children, especially when asthma is uncontrolled and during exacerbations.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“… 41 Moreover, significant differences in FeNO were seen between different asthma control groups. 41 Additionally, other studies indicated that FeNO values were related to several markers of asthma control, such as nighttime symptoms, beta-agonist use, and bronchodilator reversibility, 42 as well as to the use of oral or inhaled steroid treatment. 43 In addition, previous studies showed that FeNO was raised in asthmatic children, especially when asthma is uncontrolled and during exacerbations.…”
Section: Discussionmentioning
confidence: 97%
“… 38 Although, FeNO-guided asthma management was shown previously to have promising benefits, most clinical trials had variable effectiveness. 40 , 41 In a Meta‐analysis study, FeNO‐guided asthma management strategy was shown to partially improve the outcomes of pediatric asthma by reducing asthma exacerbations and improving the forced expiratory volume in a second (FEV1), at the expense of increased ICS dose without any beneficial effects on symptom control, quality of life. 39 In the setting of chronic inflammatory airway disease including asthma, conventional tests such as FEV1, reversibility or provocation tests are indirectly associated with airway inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…No significant correlations were observed between EVI and impulse oscillometry, baseline parameters or C-ACT scores. However, two other studies have found only weak correlations between asthma test scores and both fractional exhaled nitric oxide and forced expiratory volume in the first second of a spirometry test [8,9] The strength of our study was that patients were monitored for 6 months. The relatively mild patient population could also be considered a strength, because for those children the diagnosis of asthma is clinically challenging and lung function tests would be especially for this patient group.…”
Section: Research Letter: Inhaled Corticosteroid Treatment For Improved Expiratory Variability Index In Steroid-naive Asthmatic Childrenmentioning
confidence: 89%
“…No significant correlations were observed between EVI and impulse oscillometry, baseline parameters or C-ACT scores. However, two other studies have found only weak correlations between asthma test scores and both fractional exhaled nitric oxide and forced expiratory volume in the first second of a spirometry test [ 8 , 9 ].…”
mentioning
confidence: 99%
“…A systemic review of 58 studies revealed a weak association between FeNO levels and asthma control in adults and children ( 28 ). Nevertheless, Nguyen et al reported associations between FeNO and Asthma Control Test (ACT) score in 410 adults ( 29 ). Stern et al observed associations of FeNO with symptom scores in 151 atopic asthmatic children during 192 days when the use of inhaled corticosteroids (ICS) was adjusted every 3 weeks according to FeNO value ( 30 ).…”
Section: Discussionmentioning
confidence: 99%